"Such elements do not belong in an ordered society": Managing rural–urban resettlement in democratic South Africa. (5th July 2019) - Levenson, Zachary
Abstract: In South Africa, the scale of rural–urban resettlement after apartheid continues to overwhelm the capacity of the government to house city dwellers in need of shelter. But the legitimacy of the postapartheid government rests on its ability to secure the rights of citizens who enjoy constitutional guarantees, including the right to housing. Because the government cannot simply repress this unhoused surplus population, it seeks instead to delegitimize some portion of it. It does so by developing a number of moralizing discourses, the subject of this paper, which distinguish between patient, deserving citizens, and unruly queue jumpers perceived to threaten the democratic project itself. Housing officials misrecognize squatters as a cause, rather than a consequence, of the state's failure to deliver, policing new land occupations with a draconian severity. They justify such repression in the name of protecting the democratic order, which is assumed to require waiting instead of improvisation.